Application partitioning and mapping for bypass channel based NoC. (October 2018) - Khodaparast, Fatemeh; Reshadi, Midia; Bagherzadeh, Nader
Highlights: BC-NoC is an efficient method to reduce network packet latency. Proposed RIP BC-NoC partitioning method enhances workload consolidation density. Task communication minimally uses other application resources. Application tasks can be mapped close to each other in a straight path. Increased consolidation density & reduced latency improve performance parameters. Abstract: The network on a chip (NoC) is considered as the main shared communication resource to avoid compromise the system performance. A strict isolation strategy is employed in the NoC to avoid performance degradation; however, this strategy is accompanied by a low consolidation density or a complex routing mechanism, which leads to considerable latency and high hardware costs. We propose the row irregular partitioning (RIP) method, which results in a high consolidation density compared to regularity-oriented topology. We additionally propose a congestion awareness (CA) mapping scheme in which mapping is performed based on congestion control on a route in a bypass-channel-based NoC (BC-NoC). Furthermore, mapping methods, such as straight path (SP) and straight path and congestion awareness (SP&CA), are recommended to exploit the communication platform properties of BC-NoC. The experimental results show that the average delay in the SP mapping method is improved compared with SP&CA and CA.